Peningkatan Kemampuan Literasi Matematika Siswa Melalui Penerapan Model Pembelajaran Problem Based Learning Di Kelas VII SMPIT Insan Harapan - Ela Nurlaela; Adi Ihsan Imami (Jurnal Ilmiah Dikdaya, 2022)
This study uses the Problem Based Learning (PBL) learning model. The purpose of this study is to determine the level of students' mathematical literacy skills before and after it is applied to students of SMPIT Insan Harapan. This research method is quantitative and the type of research is Quasi Experiment with the research design of One Group Pretest-Post-test Design. The analysis technique of this research is descriptive statistics and inferential analysis statistics. The results of this study indicate that by applying the PBL learning model there is an increase in the mathematical literacy ability of SMPIT Insan Harapan students. % in the medium category. Then the percentage increased after the PBL learning model was applied, namely 20% in the medium category and 90% in the high category. The results of inferential statistical analysis (Paired Sample T-test) obtained a significant value <0.05, which means, there is an increase in students' mathematical literacy skills after the application of the PBL learning model in class VII D SMPIT Insan Harapan.